Silicon isotopes in Arctic and sub-Arctic glacial meltwaters: the role of subglacial weathering in the silicon cycle. (14th August 2019) - Hatton, Jade E.; Hendry, Katharine R.; Hawkings, Jonathan R.; Wadham, Jemma L.; Opfergelt, Sophie; Kohler, Tyler J.; Yde, Jacob C.; Stibal, Marek; Žárský, Jakub D.
Abstract : Glacial environments play an important role in high-latitude marine nutrient cycling, potentially contributing significant fluxes of silicon (Si) to the polar oceans, either as dissolved silicon (DSi) or as dissolvable amorphous silica (ASi). Silicon is a key nutrient in promoting marine primary productivity, contributing to atmospheric CO2 removal. We present the current understanding of Si cycling in glacial systems, focusing on the Si isotope (δ 30 Si) composition of glacial meltwaters. We combine existing glacial δ 30 Si data with new measurements from 20 sub-Arctic glaciers, showing that glacial meltwaters consistently export isotopically light DSi compared with non-glacial rivers (+0.16‰ versus +1.38‰). Glacial δ 30 SiASi composition ranges from −0.05‰ to −0.86‰ but exhibits low seasonal variability. Silicon fluxes and δ 30 Si composition from glacial systems are not commonly included in global Si budgets and isotopic mass balance calculations at present. We discuss outstanding questions, including the formation mechanism of ASi and the export of glacial nutrients from fjords. Finally, we provide a contextual framework for the recent advances in our understanding of subglacial Si cycling and highlight critical research avenues for assessing potential future changes in these environments.